Lethal Weapon 2 - Donner, Richard, 1930-; Glover, Danny, 1946-; Darlene Love; Derrick O'Connor; Joe Pesci; Joss Ackland; Patsy Kensit; Mel Gibson (USA Silver Pictures, 1989)
Riggs and Murtaugh are at it again in this sequel to the original Lethal Weapon in 1987. When a red BMW crashes while they are chasing it, they discover the trunk is full of South African Krugerands. Their boss assigns them to protect a federal witness named Leo Getz to try and keep them out of trouble. When the witness reveals he has been doing business with South Africans, the story evolves into a fast moving chase.
Riggs and Murtaugh are on the trail of South African diplomats who are using their immunity to engage in criminal activities.
Shane Black
Language(s): English, German, Spanish Subtitle(s): English, German, Spanish, Dutch, Swedish, Norwegian, Danish, Finnish, Portoguese, Hebrew, Polish, Greek, Czech, Turkish, Hungarian, Icelandic, Serbo-Croatian, French, Italian
Keywords: Comedy; Crime; Drama; Thriller; Action